Gender in Jeopardy!: The Role of Opponent Gender in High-Stakes Competition - Michael Jetter; Jay K. Walker (Institute for the Study of Labor (IZA), 2016)
Using 4,279 episodes of the popular US game show Jeopardy!, we analyze whether the opponents' gender is able to explain the gender gap in competitive behavior. Our findings indicate that gender differences disappear when women compete against men. This result is surprising, but emerges with remarkable consistency for the probability to (i) respond, (ii) respond correctly, and (iii) respond correctly in high-stakes situations. Even risk preferences in wagering decisions, where gender differences are especially pronounced, do not differ across gender once a woman competes against males. Using a fixed-effects framework, and therefore exploiting within-player variation only, confirms these findings. These results, derived from a large real-life setting, suggest that gender differences in performance and risk attitudes are not gender-inherent, but rather emerge in distinct social environments.
Keywords: D03; J10; J16; 330; competition; gender gap; risk preferences